DIGITAL TRANSFORMATION OF INDRAMAYU MSMES WITH DIGITAL MARKETING APPROACH: STRATEGIC STEPS TOWARDS THE 17 SUSTAINABLE DEVELOPMENT GOALS (SDG’S) - hermawan, Sabo; Fadlullah, Fauzan; Aditya, Shandy; Suhendry, Bayu; Nur Rahmawati, Alifah; Seno Adriano, Cornellius (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2025)
This study assesses the efficacy of training, mentorship, and evaluation programs in facilitating the digital transformation of MSMEs in Indramayu through the use of digital marketing, in alignment with the Sustainable Development Goals (SDGs). The curriculum encompasses SEO, social networking, e-commerce, and digital business management. The methods for assessing immediate understanding during direct presentations included observation of responses during interactive discussions and evaluations of conceptual knowledge demonstrated in real-time. Results indicate a clear improvement in the participants' conceptual understanding observed during the presentation sessions. Furthermore, a significant number of participants out of 26 successfully established online enterprises as a result of the overall program. Participation reached 90%, with 92% of respondents expressing high satisfaction and enthusiasm for future sessions. The digital transformation initiative enhances local economic competitiveness and contributes directly to SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure). The report advocates for the expansion of similar programs to accelerate digital inclusion among MSMEs and promote sustainable development.